PENGARUH MOTIVASI, LINGKUNGAN KERJA, NILAI SOSIAL, DAN KECERDASAN ADVERSITY TERHADAP MINAT MAHASISWA UNTUK MENJADI AKUNTAN PUBLIK - Zulaika, Yesi Febri; Sari, Dyah Pravita (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
Public accounting is currently in demand due to the growth of both the corporate world and the economy. The progress of today's era requires an increase in accountability and transparency in every presentation of financial statements as a part of the responsibility of public accountants. Although there is a growing need for accounting services, Indonesia is not seeing a corresponding rise in the number of accountants. This study uses workplace characteristics, societal values, motivational factors, and adversity intelligence to determine accounting students' desire to become public accountants. This study is quantitative in nature. This study focused on Sayyid Ali Rahmatullah Tulungagung State Islamic University's Sharia Accounting students. Saturation sampling and a non-probability sampling approach are used to identify the samples. One hundred respondents served as the sample size for this investigation and were surveyed with a Likert-scaled questionnaire. The study's findings show that Sayyid Ali Rahmatullah Tulungagung State Islamic University accounting students are more interested in becoming public accountants when motivated and have adversity intelligence.